The Patient-Centered Approach: A Review of the Literature and Its Application for Acoustic Neuromas - Hong, Christopher S.; Moliterno, Jennifer (Journal of Neurological Surgery Part B: Skull Base, 2020)
Patient-centered care is defined as “care that is consistent with and respects the values, needs, and wishes of patients” and is best achieved when clinicians involve patients and their support system in health care discussions and decisions. While this approach has been well established and supported in more general medical specialties, such as primary care, that may encompass a more holistic approach, it has rarely been described in surgical disciplines. Acoustic neuromas (ANs) can be unique among other skull base and intracranial pathologies, in that the management of these tumors can vary from patient to patient depending on various factors. Moreover, typical options, including observation, radiation, and surgery, may often have equipoise for some patients and their tumors. Therefore, a patient-centered approach, strongly guided by the expertise of experienced skull base surgeons, may likely be the most appropriate type of care for patients with ANs. Herein, we review the documented use of patient-centered care in other aspects of medicine, propose the benefits of this approach for patients with ANs, and provide ways this can be better implemented in practice.
Keywords: acoustic neuroma; patient-centered care; patient preferences